Coal gangue-based solid waste cementing material as well as preparation method and application thereof

By using coal gangue-based solid waste gelling materials, the problems of high energy consumption and waste of coal gangue resources in the production process of traditional base materials are solved, and the large-scale application of coal gangue solid waste and the high mechanical performance and durability requirements of high road engineering base materials are achieved.

CN119638285APending Publication Date: 2025-03-18宁夏交通建设股份有限公司 +2
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411805380.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing base materials such as cement and lime have high energy consumption and large emissions in the production process, which is not conducive to sustainable development. How to use coal gangue to prepare highway engineering base materials with good mechanical properties and durability is still a research difficulty.

Method used

The coal gangue-based solid waste gelling material is used, and the raw materials for preparation include activated coal gangue powder, exciters, slag powder, silicon fume, gypsum and fan blade staple fibers. By calcining the coal gangue powder and mixing it with other materials, a gelling material with high mechanical properties and durability is formed.

Benefits of technology

It has realized the large-scale application of coal gangue solid waste, reduced the difficulty of material production and thermal energy use, and the material has the advantages of low early strength, continuous growth of later strength, retarding, micro-expansion and resistance to sulfate erosion, and meets the use requirements of the grassroots of highway engineering projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638285A_ABST
    Figure CN119638285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of civil engineering materials, and particularly relates to a coal gangue-based solid waste cementing material as well as a preparation method and application thereof. The coal gangue-based solid waste cementing material is prepared from the following raw materials in percentage by mass: 60-80% of activated coal gangue powder, 5-20% of an exciting agent, 5-15% of superfine slag powder, 2-5% of silica fume, 1-3% of gypsum and 1-3% of fan blade short fibers. According to the invention, solid waste resources (coal gangue and superfine slag powder) are recycled, and on the basis of consumption of the solid waste resources, the coal gangue-based solid waste cementing material obtained by using the solid waste resources has good mechanical properties and durability, and can meet the use requirements of highway engineering base layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of civil engineering materials, and in particular relates to a gangue-based solid waste cementitious material and a preparation method and application thereof. Background Art

[0002] With the rapid development of highway construction, the demand for base materials is growing. Although traditional base materials such as cement and lime are widely used, their production process has high energy consumption and large emissions, which is not conducive to sustainable development. Coal gangue is a black-gray rock with low carbon content and high hardness that coexists with coal seams during the coal formation process. The rampant stacking of coal gangue has caused serious waste of resources and land occupation. If the solid waste resource of coal gangue is used in a high-value way, it will not only reduce the land occupied by solid waste, but also benefit environmental protection. However, how to use coal gangue to prepare highway engineering base materials with good mechanical properties and durability is still a difficulty in current research. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a gangue-based solid waste cementitious material and a preparation method and application thereof. The gangue-based solid waste cementitious material obtained by the present invention from solid waste resources (gangue) has good mechanical properties and durability, and can meet the use requirements of the base layer of highway engineering.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention provides a gangue-based solid waste cementitious material, comprising the following raw materials in percentage by weight:

[0006] 60-80% activated coal gangue powder, 5-20% activator, 5-15% slag powder, 2-5% silica fume, 1-3% gypsum, and 1-3% fan blade short fiber.

[0007] Preferably, the activator comprises sulfate, sodium hydroxide and additives; the mass percentages of sulfate, sodium hydroxide and additives in the activator are 20-30%, 50-60% and 15-30% respectively.

[0008] Preferably, the short fibers of the fan blades have a length of 5 to 7 mm, a diameter of 0.3 to 0.6 mm, and an aspect ratio of 20 to 40:1.

[0009] Preferably, the particle size of the slag powder is ≤80 μm, the 45 μm sieve residue is ≤30%, and the specific surface area is ≥400 m 2 / kg.

[0010] Preferably, the preparation method of the activated coal gangue powder is: calcining and activating the coal gangue powder to obtain the activated coal gangue powder;

[0011] The calcination activation temperature is 400-1100° C.; the calcination activation time is 30-150 minutes.

[0012] Preferably, the 45 μm sieve residue of the coal gangue powder is ≤30%, and the specific surface area is ≥300 m 2 / kg.

[0013] Preferably, the particle size of the silica fume is ≤110 μm and the specific surface area is ≥15 m 2 / g.

[0014] Preferably, the additives include a water reducing agent and an expansion agent.

[0015] The present invention also provides a method for preparing the gangue-based solid waste cementitious material described in the above technical solution, comprising the following steps:

[0016] The activated coal gangue powder, an activator, slag powder, silica fume, gypsum and fan blade short fibers are mixed to obtain the coal gangue-based solid waste cementitious material.

[0017] The present invention also provides the use of the gangue-based solid waste cementitious material described in the above technical solution or the gangue-based solid waste cementitious material prepared by the preparation method described in the above technical solution in base materials for highway engineering.

[0018] The invention provides a gangue-based solid waste cementitious material, comprising the following raw materials in percentage by weight: 60-80% of activated gangue powder, 5-20% of activator, 5-15% of slag powder, 2-5% of silica fume, 1-3% of gypsum and 1-3% of fan blade short fibers. The activated gangue powder in the present invention can ensure the activity of the gangue-based solid waste cementitious material. The activated gangue reacts with other materials to form a large amount of amorphous hydration products such as hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH), which promotes the formation of a crystalline product, calcium sulfonate (AFt). At the same time, with the increase of calcination temperature, the Ca(OH)2 content in the activated gangue gradually decreases, that is, the activated substances in the activated gangue undergo a secondary hydration reaction; the activator is used to further activate the active components (metakaolinite) in the gangue to improve the mechanical properties of the gangue-based solid waste cementitious material; slag powder, silica fume and gypsum are used as auxiliary admixtures of the overall cementitious material, which can further improve the mechanical properties and durability of the gangue-based solid waste cementitious material and play the role of a functional additive therein. The mineral powder is mainly the active SiO2, Al2O3 and OH - 、SO 2-4. The plasma reaction generates CSH and CASH gels, which play a role in enhancing mechanical properties and also play a filling role in cementitious materials; the fine particles of silica fume can fill the gaps between the particles of coal gangue powder, improve the compactness of the cementitious system, thereby significantly improving its compressive strength, and can improve the semi-rigid base layer's resistance to chloride ion penetration, thereby extending the service life of the semi-rigid base layer; gypsum plays a role in regulating the setting time in the entire system, and also promotes the hydration reaction of the cementitious system, converting hydrated calcium silicate into tobermorite, further enhancing the stability and durability of the material; the short fibers of the fan blades can improve the anti-bending and tensile properties of coal gangue-based solid waste cementitious materials applied to semi-rigid base layers. The present invention reuses solid waste resources (coal gangue, slag powder), and on the basis of absorbing solid waste resources, the coal gangue-based solid waste cementitious materials obtained by using solid waste resources have low early strength, continuous growth in late strength, and slow setting, which can extend the construction allowable time, micro-expansion, can reduce base cracking, and also have the effect of resisting sulfate erosion. Therefore, gangue-based solid waste cementitious materials have good mechanical properties and durability, and can meet the use requirements of highway engineering base layers.

[0019] The present invention also provides a method for preparing the above-mentioned gangue-based solid waste cementitious material. Compared with traditional cement-based materials, when ordinary silicate clinker is prepared, the raw material is calcined and cooled at 1400-1450°C. The present invention uses gangue and other solid waste materials as the matrix, and the temperature required for the calcination activation reaction of the gangue is relatively low (≤1100°C). The subsequent mixing of multiple materials only requires cold mixing, which greatly reduces the use of thermal energy and the difficulty of material production. While ensuring that the mechanical properties meet the relevant regulations, the large-scale application of gangue solid waste is achieved, and the large-scale application of gangue industrial solid waste is truly achieved. In addition, the preparation method of the present invention is simple and low in cost, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are the XRD patterns of highway engineering base materials prepared from activated coal gangue powder obtained at different calcination activation temperatures. DETAILED DESCRIPTION

[0021] The present invention provides a gangue-based solid waste cementitious material, comprising the following raw materials in percentage by weight:

[0022] 60-80% activated coal gangue powder, 5-20% activator, 5-15% slag powder, 2-5% silica fume, 1-3% gypsum, and 1-3% fan blade short fiber.

[0023] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.

[0024] The raw material for preparing the gangue-based solid waste gelling material provided by the present invention comprises 60-80% by mass of activated gangue powder, preferably 70-75% by mass. The 45 μm sieve residue of the activated gangue powder is preferably ≤30%.

[0025] In the present invention, the preparation method of the activated coal gangue powder is preferably: calcining and activating the coal gangue powder to obtain the activated coal gangue powder. In the present invention, the temperature of the calcination and activation is preferably 400-1100°C, more preferably 800-1000°C, and most preferably 900°C; the time of the calcination and activation is preferably 30-150 minutes, more preferably 40-90 minutes; the equipment used for the calcination and activation is preferably a muffle furnace, a calcining furnace or a rotary kiln, and more preferably a calcining furnace.

[0026] In the present invention, the 45 μm sieve residue of the coal gangue powder is preferably ≤30%, more preferably ≤10%; the specific surface area of ​​the coal gangue powder is preferably ≥300 m 2 / kg; the preparation method of the coal gangue powder is preferably: the coal gangue is subjected to coarse crushing, fine crushing and grinding in sequence to obtain the coal gangue powder; the equipment used for the coarse crushing and fine crushing is preferably a crusher, more preferably a jaw crusher; when the coarse crushing is performed, the diameter of the discharge port of the crusher is preferably 40mm, and the coarse crushing is preferably performed by crushing the coal gangue to obtain a mixed material with a particle size of ≤40mm; when the fine crushing is performed, the diameter of the discharge port of the crusher is preferably 10mm, and the fine crushing is preferably performed by crushing the mixed material obtained by the coarse crushing to a particle size of ≤10mm; the grinding rate is preferably ≥400rpm, more preferably ≥450rpm; the grinding time is preferably ≥5min, more preferably ≥8min; the equipment used for the grinding is preferably a ball mill. In the present invention, the grinding time is determined according to the material of the coal gangue actually used.

[0027] The fineness of the coal gangue powder in the present invention meets the requirements of cementitious materials commonly used in the highway industry, and the 45μm sieve residue is ≤30%, so as to ensure the activity of the coal gangue-based solid waste cementitious material.

[0028] The main mineral phases of uncalcined and 400℃ calcined coal gangue powder are mainly crystalline minerals of kaolinite and quartz. However, as the temperature increases, the internal quartz phase gradually transforms, and the kaolinite inside the coal gangue can be transformed into metakaolinite with volcanic ash activity after calcination and activation.

[0029] Compared with traditional cement-based materials, when ordinary silicate clinker is prepared, the raw material is calcined and cooled at 1400-1450°C. The present invention uses coal gangue and other solid waste materials as the matrix, and the temperature required for the calcination activation reaction of the coal gangue is relatively low (≤1100°C). The subsequent mixing of multiple materials only requires cold mixing, which greatly reduces the use of thermal energy and the difficulty of material production. While ensuring that the mechanical properties meet the relevant regulations, the large-scale application of coal gangue solid waste is realized, and the large-scale application of coal gangue industrial solid waste is truly realized. In addition, the preparation method of the present invention is simple and low in cost, which is conducive to promotion and application.

[0030] The raw materials for preparing the gangue-based solid waste cementitious material provided by the present invention include an activator with a mass percentage of 5 to 20%, preferably 8 to 12%. In the present invention, the activator preferably includes sulfate, sodium hydroxide and additives; the additives preferably include a water reducer and an expander; the water reducer is preferably a polycarboxylic acid powder water reducer; the particle size of the polycarboxylic acid powder water reducer is preferably ≤150μm; the expander is preferably a magnesium expander; the particle size of the expander is preferably ≤80μm; the mass percentages of sulfate, sodium hydroxide and additives in the activator are preferably 20 to 30%, 50 to 60% and 15 to 30%, respectively, and more preferably 25 to 30%, 55 to 60% and 15 to 20%.

[0031] The water reducing agent reduces the water demand of the cementitious material, and the expansive agent plays a role of micro-expansion, compensating for the later shrinkage of the cementitious material.

[0032] The activator used in the present invention is used to activate active components in coal gangue to improve the gelling properties of the coal gangue-based solid waste gelling material.

[0033] The raw materials for preparing the gangue-based solid waste cementitious material provided by the present invention include 5-15% by mass of slag powder, preferably 10-15%. In the present invention, the particle size of the slag powder is preferably ≤80μm, the 45μm sieve residue is preferably ≤30%, more preferably ≤10%; the specific surface area of ​​the slag powder is preferably>400m 2 / kg; the activity grade of the slag powder is preferably ≥S95.

[0034] The raw materials for preparing the gangue-based solid waste cementitious material provided by the present invention include 2-5% by mass of silica fume, preferably 3-4%. In the present invention, the particle size of the silica fume is preferably ≤110 μm, more preferably 0.7-110 μm, the 45 μm sieve residue of the silica fume is preferably ≤10%, more preferably ≤2%; the specific surface area (BET method) of the silica fume is preferably ≥15 m 2 / g.

[0035] The raw materials for preparing the gangue-based solid waste cementitious material provided by the present invention include gypsum with a mass percentage of 1 to 3%, preferably 2 to 3%; the gypsum is preferably industrial by-product gypsum, more preferably desulfurized gypsum and / or phosphogypsum. In the present invention, the particle size of the gypsum is preferably ≤300 μm, more preferably ≤150 μm, and the 80 μm sieve residue of the gypsum is ≤30%.

[0036] In the present invention, slag powder, silica fume and gypsum are all powder products, which, as auxiliary admixtures of the overall cementitious material, can further improve the mechanical properties and durability of the gangue-based solid waste cementitious material, thereby playing the role of functional additives.

[0037] The raw material for preparing the coal gangue-based solid waste cementitious material provided by the present invention comprises 1-3% by mass of fan blade short fibers, preferably 2-3%. In the present invention, the fan blade short fibers are preferably 5-7 mm in length, more preferably 6-7 mm in diameter, preferably 0.3-0.6 mm in diameter, more preferably 0.3-0.4 mm in aspect ratio, preferably 20-40:1, more preferably 20-30:1 in aspect ratio.

[0038] The short fibers of wind turbine blades in the present invention are products recycled after the service life of wind turbine blades is reached, and belong to thermosetting composite materials (thermosetting resin reinforced with glass fiber (GF), carbon fiber (CF) or GF / CF mixture); wind turbine blades can no longer be melted or reshaped due to cross-linking reactions, and the use of traditional treatment methods (open-air stacking, landfill or incineration) limits the rational reuse of resources and causes certain environmental pollution; therefore, the composite materials are chopped or ground into block particles, short fibers and other materials of different sizes through a mechanical recycling method, among which the short fibers of wind turbine blades can improve the bending and tensile properties of coal gangue-based solid waste cementitious materials used in semi-rigid base layers.

[0039] The present invention also provides a method for preparing the gangue-based solid waste cementitious material described in the above technical solution, comprising the following steps:

[0040] The activated coal gangue powder, an activator, slag powder, silica fume, gypsum and fan blade short fibers are mixed to obtain the coal gangue-based solid waste cementitious material.

[0041] In the present invention, the activated coal gangue powder, activator, slag powder, silica fume, gypsum and fan blade short fibers are preferably mixed as follows: the activated coal gangue powder, activator, slag powder, silica fume and gypsum are first mixed, and fan blade short fibers are added to the obtained first mixture for second mixing; the first mixing and the second mixing are preferably carried out under stirring conditions; the stirring rate is preferably 95-145rpm, more preferably 100-140rpm; the first mixing time is preferably 1-3min, more preferably 2-3min; the second mixing time is preferably 3-5min, more preferably 5min; the fan blade short fibers are all added within 30s, more preferably within 15-20s.

[0042] The present invention also provides the use of the gangue-based solid waste cementitious material described in the above technical solution or the gangue-based solid waste cementitious material prepared by the preparation method described in the above technical solution in base materials for highway engineering.

[0043] In the present invention, the highway engineering base material preferably includes gangue-based solid waste cementitious material, water and aggregate; the mass ratio of the aggregate, gangue-based solid waste cementitious material and water is preferably 100:2-6:2-6, more preferably 100:3-5:3-5. The present invention has no special limitation on the particle size range of the graded crushed stone, which can be selected according to actual conditions.

[0044] The gangue-based solid waste cementitious material provided by the present invention meets the various index requirements of the current highway engineering standard GB / T35162-2017 "Slow-setting Portland Cement for Road Base", and the highway engineering base prepared using it has good mechanical properties and durability, and can meet the use requirements of the highway engineering base.

[0045] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] First, adjust the jaw crusher discharge port diameter to 40mm, and crush the gangue raw material (lump) into a mixture with a particle size of ≤40mm. Then adjust the crusher discharge port diameter to 10mm, and crush it into a fine-particle mixture with a particle size of ≤10mm.

[0048] Add the fine particle size mixture into a ball mill and grind it at 400 rpm for 5 minutes to obtain coal gangue powder with a 45 μm sieve residue rate of ≤30%;

[0049] Adding the coal gangue powder into a muffle furnace and calcining and activating it at 900° C. for 1.5 hours to obtain activated coal gangue powder;

[0050] The activated coal gangue powder is first mixed with an activator, slag powder, silica fume and gypsum, and stirred at 100 rpm for 3 minutes. The fan blade short fibers are added to the first mixture for second mixing, and stirred at 140 rpm for 5 minutes to obtain a coal gangue-based solid waste cementitious material;

[0051] The mass percentages of the used coal gangue powder, activator, slag powder, silica fume, gypsum and fan blade short fibers are 70:8:12:4:3:3 respectively;

[0052] The activator is composed of 30% sulfate, 55% sodium hydroxide and 15% additives (polycarboxylic acid powder water reducer with a particle size of ≤150μm and magnesium expansion agent with a particle size of ≤80μm); the particle size of the slag powder is ≤80μm, the 45μm sieve residue is ≤30%, and the specific surface area is ≥400m 2 / kg, activity grade ≥ S95; the particle size of the silica fume is 0.7-110 μm, and the 45 μm sieve residue is ≤10%, and the specific surface area (BET method) is ≥15m 2 / g; the particle size of the gypsum (desulfurized gypsum) is ≤300μm, and the 80μm sieve residue is ≤30%; the length of the fan blade short fiber is 7mm, the diameter is 0.3mm, and the aspect ratio is 23:1;

[0053] The analysis results of various raw material components in Example 1 are shown in Table 1.

[0054] Table 1 Raw material composition analysis

[0055]

[0056] Embodiments 2 to 8

[0057] The difference between Examples 2 to 8 and Example 1 is that the calcination activation temperature of the coal gangue is different from that of Example 1. The calcination activation temperature of the coal gangue in different examples is shown in Table 2.

[0058] Table 2 Calcination activation temperature of coal gangue in different embodiments

[0059]

[0060] Comparative Example 1

[0061] The difference from Example 1 is that the activated coal gangue powder is removed, and the coal gangue powder that has not been activated at high temperature is directly mixed with other materials.

[0062] According to Example 1, the gangue is crushed and ground to obtain gangue powder;

[0063] The gangue powder is directly mixed with an activator, slag powder, silica fume and gypsum without calcination and activation, and stirred at 100 rpm for 3 minutes. The fan blade short fibers are added to the first mixture for second mixing, and stirred at 140 rpm for 5 minutes to obtain a gangue-based solid waste cementitious material;

[0064] The mass percentages of the used coal gangue powder, activator, slag powder, silica fume, gypsum and fan blade short fibers are 70:8:12:4:3:3 respectively.

[0065] Activated coal gangue powder is used as the matrix of the coal gangue-based solid waste cementitious material provided by the present invention; the purpose of comparative example 1 is to evaluate the change in strength activity growth between coal gangue powder after high-temperature calcination and without high-temperature calcination.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that the slag powder is removed.

[0068] According to Example 1, the gangue is crushed and ground to obtain gangue powder;

[0069] Adding the coal gangue powder into a muffle furnace and calcining and activating it at 900° C. for 1.5 hours to obtain activated coal gangue powder;

[0070] The activated coal gangue powder is first mixed with an activator, silica fume and gypsum, and stirred at 100 rpm for 3 minutes. The fan blade short fibers are added to the first mixture for second mixing, and stirred at 140 rpm for 5 minutes to obtain a coal gangue-based solid waste cementitious material;

[0071] The mass percentages of the coal gangue powder, activator, silica fume, gypsum and fan blade short fibers used are 82:8:4:3:3 respectively.

[0072] The slag powder plays a role in enhancing the mechanical properties of the gangue-based solid waste cementitious material provided by the present invention, and also plays a filling role, and is an auxiliary admixture of the overall material; the purpose of comparative example 2 is to evaluate the effect of the auxiliary admixture on the strength growth of the gangue-based cementitious material.

[0073] Comparative Example 3

[0074] The difference from Example 1 is that the activator is removed.

[0075] According to Example 1, the gangue is crushed and ground to obtain gangue powder;

[0076] Adding the coal gangue powder into a muffle furnace and calcining and activating it at 900° C. for 1.5 hours to obtain activated coal gangue powder;

[0077] The activated coal gangue powder is first mixed with slag powder, silica fume and gypsum, and stirred at 100 rpm for 3 minutes, and then fan blade short fibers are added to the obtained first mixture for second mixing, and stirred at 140 rpm for 5 minutes to obtain a coal gangue-based solid waste cementitious material;

[0078] The mass percentages of the coal gangue powder, slag powder, silica fume, gypsum and fan blade short fibers used are 78:12:4:3:3 respectively.

[0079] The activator can make some active components (such as metakaolinite) in the gangue appear through a chemical activation process. The purpose of comparative example 3 is to evaluate the effect of the activator on the early strength growth of the gangue-based cementitious material.

[0080] Comparative Example 4

[0081] The difference from Example 1 is that the gypsum is removed.

[0082] According to Example 1, the gangue is crushed and ground to obtain gangue powder;

[0083] Adding the coal gangue powder into a muffle furnace and calcining and activating it at 900° C. for 1.5 hours to obtain activated coal gangue powder;

[0084] The activated gangue powder is first mixed with an activator, slag powder and silica fume, and stirred at 100 rpm for 3 minutes. The fan blade short fibers are added to the first mixture for second mixing, and stirred at 140 rpm for 5 minutes to obtain a gangue-based solid waste cementitious material;

[0085] The mass percentages of the used coal gangue powder, activator, slag powder, silica fume and fan blade short fibers are 73:8:12:4:3 respectively.

[0086] Gypsum in the cementitious material can prolong the setting time (thereby improving the convenience of construction), and has the characteristic of micro-expansion (this characteristic can compensate for the partial shrinkage of the base material after the construction is completed, thereby reducing the occurrence of cracks in the project); the purpose of comparative example 4 is to demonstrate the contribution of auxiliary admixtures to the overall functionality of coal gangue-based cementitious materials.

[0087] Application Example 1

[0088] The gangue-based solid waste cementitious material prepared in Example 1, water and aggregate were mixed in the proportions shown in Table 3 to obtain a highway engineering base material.

[0089] Table 3 Ingredients of highway engineering base materials

[0090]

[0091] Application Examples 2 to 8

[0092] The difference from Application Example 1 is that the gangue-based solid waste cementitious material prepared in Example 1 is replaced by the gangue-based solid waste cementitious materials prepared in Examples 2 to 8 respectively.

[0093] Performance Testing

[0094] (1) Conducting activity tests on uncalcined coal gangue powder and activated coal gangue powder prepared in Examples 1 to 7 to obtain activity indexes;

[0095] Test method: According to T0506-2005 "Test Method for Strength of Cement Mortar (ISO Method)" in JTG / 3420-2020 "Test Procedure for Cement and Cement Concrete for Highway Engineering", the strength test piece of the comparative cement is formed alone (cement: water: standard sand is mixed at a ratio of 1:0.5:3 according to the specified mixing rate and time, and injected into a mortar standard triple test mold of 40mm×40mm×160mm, demolded and cured after solidification, and strength test is carried out after reaching the age);

[0096] Comparative cement: Portland cement or ordinary Portland cement with strength grade of 42.5 as specified in GB 175, and 3d compressive strength of 25-35MPa, 7d compressive strength of 35-45MPa, 28d compressive strength of 50-60MPa, specific surface area of ​​350-400m 2 / kg, SO3 content (mass fraction) 2.3~2.8%, alkali content (Na2O+0.658K2O) (mass fraction) 0.5~0.9%.

[0097] The gangue powder and the comparative cement were mixed according to Table 4 to form strength test pieces;

[0098] After reaching the specified age, the strength of the comparison mortar and the test mortar is tested in accordance with T 0506-2005 "Test Method for Strength of Cement Mortar (ISO Method)", and the strength is compared with the comparison mortar strength. The test data are as follows:

[0099] Table 4 Activity test method

[0100]

[0101] The 7-day activity index of coal gangue is calculated according to formula 1, and the calculation result is rounded to the integer:

[0102]

[0103] Where:

[0104] A1—coal gangue powder, 7d activity index, %;

[0105] R01 —Comparison of 7d compressive strength of mortar, in megapascals (MPa);

[0106] R1—7d compressive strength of test mortar, in megapascals (MPa).

[0107] The 28d activity index of coal gangue is calculated according to formula 2, and the calculation result is rounded to the integer:

[0108]

[0109] Where:

[0110] A 28 —Gangue powder, 28d strength activity index, %;

[0111] R—28d compressive strength of test mortar, in megapascals (MPa);

[0112] R0—28d compressive strength of comparison mortar, in megapascals (MPa).

[0113] The test results are shown in Table 5.

[0114] Table 5 Activated coal gangue activity test results

[0115]

[0116] As shown in Table 5, the activity index of coal gangue powder increases significantly after calcination. The activated coal gangue reacts with other materials to form a large number of amorphous hydration products such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), which promotes the formation of crystalline product ettringite (AFt). At the same time, with the increase of calcination temperature, the Ca(OH)2 content in the activated coal gangue gradually decreases, that is, the activated substances in the activated coal gangue undergo secondary hydration reaction. However, when the temperature reaches a certain level, the mineral types of coal gangue will decrease, ferric oxide will be produced, and minerals such as aluminum sulfate will disappear, which is not conducive to the growth of hydration strength.

[0117] Therefore, it can be concluded that the hydration effect of coal gangue is best after being activated at a high temperature of 800-900℃.

[0118] Table 6 Performance of gangue-based solid waste cementitious materials prepared in Example 1 and Comparative Examples 1 to 4

[0119]

[0120] As can be seen from Table 6, compared with Example 1, it can be clearly found that whether the gangue is not activated, the slag powder is removed, the activator is not used, or the gypsum is removed, whether one or more of the above components are removed, it will directly and significantly affect the overall performance of the solid waste-based cementitious material. Specifically, adding unactivated gangue will significantly weaken the 7-day compressive strength of the material; if the slag powder is removed, the strength of the two different ages will not meet the standard requirements; if the activator is not added, it will directly lead to the early compressive strength not meeting the standard; removing gypsum will shorten the setting time of the material and make the linear expansion rate unable to meet the established requirements.

[0121] (2) X-ray diffractometer (XRD) was used to analyze the phase composition of highway engineering base materials prepared using activated coal gangue powder obtained at different calcination activation temperatures. The results are as follows: Figure 1 shown.

[0122] Depend on Figure 1 It can be seen that with the increase of temperature, a large number of amorphous hydration products are formed: such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), which promote the formation of crystalline product ettringite (AFt) and consume the crystalline product calcium hydroxide (Ca(OH)2). At the same time, it can be found that with the increase of calcination temperature, the Ca(OH)2 content in the activated coal gangue gradually decreases, that is, the activated substances in the activated coal gangue undergo secondary hydration reaction.

[0123] The Ca(OH)2 produced by hydration will further react with the active SiO2 and Al2O3 in the activated coal gangue to generate CSH and CAH gels, and Al2O3 will also react with Ca(OH)2 and CaSO4 to generate AFt. These secondary hydration products will fill the pores in the cement matrix, optimize the pore structure of the matrix, and improve the mechanical properties of the slurry. This is also the reason why the compressive strength of the activated coal gangue specimens gradually increases in the mechanical properties test.

[0124] From the above activity test and phase analysis results, it can be seen that compared with standard cement, the activity effect of coal gangue powder is best at 900℃.

[0125] (3) Referring to the various index requirements in the current highway engineering standard GB / T 35162-2017 "Retarded silicate cement for road base", the performance of the highway engineering base material prepared using the gangue-based solid waste cementitious material in Example 1 was tested. The results are shown in Table 7.

[0126] Table 7 Performance of highway engineering base materials prepared from coal gangue-based solid waste cementitious materials

[0127]

[0128] It can be seen from Table 7 that the gangue-based solid waste cementitious material provided by the present invention meets the various index requirements of the current highway engineering standard GB / T35162-2017 "Slow-setting Portland Cement for Road Base".

[0129] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A coal gangue-based solid waste cementitious material, characterized in that: Including the following raw materials in percentage by weight: 60-80% activated coal gangue powder, 5-20% activator, 5-15% slag powder, 2-5% silica fume, 1-3% gypsum, and 1-3% fan blade short fiber.

2. The gangue-based solid waste cementitious material according to claim 1, characterized in that: The activator comprises sulfate, sodium hydroxide and additives; the mass percentages of sulfate, sodium hydroxide and additives in the activator are 20-30%, 50-60% and 15-30% respectively.

3. The gangue-based solid waste cementitious material according to claim 1, characterized in that: The short fibers of the fan blades have a length of 5 to 7 mm, a diameter of 0.3 to 0.6 mm, and an aspect ratio of 20 to 40:

1.

4. The gangue-based solid waste cementitious material according to claim 1, characterized in that: The particle size of the slag powder is ≤80μm, the 45μm sieve residue is ≤30%, and the specific surface area is ≥400m 2 / kg.

5. The gangue-based solid waste cementitious material according to claim 1, characterized in that: The preparation method of the activated coal gangue powder comprises: calcining and activating the coal gangue powder to obtain the activated coal gangue powder; The calcination activation temperature is 400-1100° C.; the calcination activation time is 30-150 minutes.

6. The gangue-based solid waste cementitious material according to claim 5, characterized in that: The 45μm sieve residue of the coal gangue powder is ≤30%, and the specific surface area is ≥300m 2 / kg.

7. The gangue-based solid waste cementitious material according to claim 1, characterized in that: The particle size of the silica fume is ≤110μm, and the specific surface area is ≥15m 2 / g.

8. The gangue-based solid waste cementitious material according to claim 2, characterized in that: The additives include a water reducing agent and an expansion agent.

9. The method for preparing the gangue-based solid waste cementitious material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The activated coal gangue powder, an activator, slag powder, silica fume, gypsum and fan blade short fibers are mixed to obtain the coal gangue-based solid waste cementitious material.

10. Use of the gangue-based solid waste cementitious material according to any one of claims 1 to 8 or the gangue-based solid waste cementitious material prepared by the preparation method according to claim 9 in base materials for highway engineering.

Citation Information

Cited By

  • Solid waste-based cementing material stable coal-based solid waste road base material and preparation method thereof

    CN121181299A

  • Solid waste-based cementitious materials, stabilized coal-based solid waste road base materials and their preparation methods

    CN121181299B

  • Geopolymer cement based on coal gangue activation reaction as well as preparation method and application of geopolymer cement

    CN121377583A